(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
A method to enhance the technological capabilities of universal grinding equipment and improve the durability of grinding wheels is proposed. A device that allows to implement this method by using of continuously variable grinding speed is proposed. This reduces the cost of manufacturing products of various structural materials.